Eliciting cytotoxic T lymphocytes against acute myeloid leukemia-derived antigens: evaluation of dendritic cell-leukemia cell hybrids and other antigen-loading strategies for dendritic cell-based vaccination. - Galea-Lauri, J; Darling, D; Mufti, G; Harrison, P; Farzaneh, F (2002)
Dendritic cells (DC) have been successfully used in clinical pilot studies to induce tumor-specific immunity as well as clinical response in selected patients. However, DC-based immunotherapy remains a challenge and several parameters need to be examined in order to optimize the induction of anti-tumor immune responses. This study focuses on DC vaccination for leukemia and evaluates the in vitro efficacy of three different strategies for generating antigen-loaded DC-based vaccines for the induction of major histocompatibility complex (MHC) class I-restricted anti-leukemia cytotoxic T lymphocyte (CTL) responses. These included direct fusion of DC with leukemia cells to generate DC-leukemia cell hybrids, and DC pulsed with either apoptotic leukemia cell fragments or whole tumor cell lysates. Using either the U937 cell line or primary human acute myeloid leukemia blasts (AML), DC-leukemia cell hybrids were found to be the most potent in vitro inducers of CTL activity. DC pulsed with apoptotic tumor cell fragments were less efficient, but induced a more potent CTL response compared to tumor lysate-pulsed DC. The CTL responses were both MHC class I-restricted and antigen-specific, as shown by the inability of the CTL to lyse other control targets. The data presented here suggest that the method of antigen loading onto DC may be critical in the design of tumor vaccines.